1993
DOI: 10.1159/000129297
|View full text |Cite
|
Sign up to set email alerts
|

PGI<sub>2</sub> Aerosol versus Nitric Oxide for Selective Pulmonary Vasodilation in Hypoxic Pulmonary Vasoconstriction

Abstract: Intravenous prostacyclin (PGI2) is a potent pulmonary vasodilator in pulmonary hypertension. However, dose-dependent systemic vasodilation, an increase in intrapulmonary shunt and hypoxemia limit its clinical application. Recently, inhaled nitric oxide (NO) has been reported to elicit selective pulmonary vasodilation, but its clinical use is restricted by its potential toxicity; furthermore, the feasibility of NO application in clinical practice seems difficult. Therefore, we investigated the effects of PGI2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1
6

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 26 publications
4
50
1
6
Order By: Relevance
“…PGI, indicating the local vasodilating effect of inhaled PGI,. In our study the inhaled PGI, dose of 30-60 nglkglmin was significantly higher than the dose applied by Welte et al (27) in dogs and slightly higher than the dose applied to humans with ARDS (26). The real aerosol deposit in the lungs is rather small (<5%) (31,32) and cannot be easily determined.…”
Section: -I -contrasting
confidence: 68%
See 2 more Smart Citations
“…PGI, indicating the local vasodilating effect of inhaled PGI,. In our study the inhaled PGI, dose of 30-60 nglkglmin was significantly higher than the dose applied by Welte et al (27) in dogs and slightly higher than the dose applied to humans with ARDS (26). The real aerosol deposit in the lungs is rather small (<5%) (31,32) and cannot be easily determined.…”
Section: -I -contrasting
confidence: 68%
“…In addition, they speculated that an increase in the dose of aerosolized PGI, might cause "spillover" of the prostanoid into the systemic circulation. In 1993 Welte et al (27) reported their investigation on the effects of PGI, aerosol on pulmonary and systemic circulation compared with NO inhalation in 6 dogs with hypoxic pulmo- …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is unlikely on the basis of other reports. 10,29,30 In children with PHT and CHD, both iNO and aerosolized iloprost are equally effective in selectively lowering pulmonary vascular resistance through a selective increase in cGMP or cAMP, respectively. However, the combination of both vasodilators failed to prove more potent than either substance alone.…”
Section: Rimensberger Et Al Comparison Of Inhaled Pulmonary Vasodilatorsmentioning
confidence: 99%
“…Intravenous PGE 1 (ivPGE 1 ) and PGI 2 , potent vasodilators used empirically in the treatment of NHRF, are associated with systemic hypotension and worsening of oxygenation due to increased venous admixture (2)(3)(4)(5)(6). This has led investigators to explore the delivery of PGE 1 and PGI 2 directly to the lungs as an inhalation, thus minimizing systemic effects and achieving selective pulmonary vasodilation (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Compared to PGI 2 , PGE 1 has a shorter half-life, lower pH (6.3 versus 10.5), bronchodilator action, anti-proliferative and anti-inflammatory effects on the alveolar, interstitial and vascular spaces of the lung (8,(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%